Gender and learning attitudes in using Web-based science lessons - Siew Chee Leong; Suliman Al-Hawamdeh (Information Research: An International Electronic Journal)
This study was carried out in a mixed gender school using the World Wide Web to teach the top primary five (11 years old) class of forty pupils using a constructivist approach to learning. The study shows differences in gender attitudes toward computers. Generally, boys spent more time with computers at home playing games and had more experience using the World Wide Web compared to girls. On the other hand, more girls preferred the Web-based lesson compared to traditional classroom-based lessons. They learnt more from paired-group work and preferred to work with a partner while boys preferred working alone and learned less working with a partner. The study also found that unlike girls, boys disliked reading from computer screens because they had difficulty reading long pages of text.